Hypertensive patient in the surgical ward - what the Surgeon should do (2004)
Two cases of hypertension are presented to emphasize the need for the surgeons to pay adequate attention to these purely medical conditions that may have a devastating adverse effect on the outcome of surgery. The article also highlights the serious constraints that still characterize the management of these patients in this part of the world. The ideal situation is a multi-disciplinary approach involving the Surgeon, the Physician and the Anaesthetist. The surgeon must not confine himself to the technical aspect of the surgery alone. The hypertension must be controlled whether the patient presents with an elective or emergent surgical condition and anti-hypertensive medication must be continued up till the time ofsurgery and at times intra-operatively. It is not only unnecessary hut also potentially dangerous to withdraw anti-hypertensives before anaesthesia. The main goal of the surgically amenable secondary hypertension is to remove the cause ofter adequate control of the hypertension in preparation for surgery. Patient however must be made to understand that the hypertension may not be "cured" and the anti-hypertensive medication may have to be continued post-operatively particularly if the hypertension is long established before patient presents. Local and/or regional blocks are to be preferred to general anaesthesiafor peripheral lesions and even then it is still preferable to have the hypertension controlled.